Influencing factors and mechanism of Cr(VI) reduction by facultative anaerobic Exiguobacterium sp. PY14 - Huang, Yunhong; Tang, Jie; Zhang, Bei; Long, Zhong-Er; Ni, Haiyan; Fu, Xueqin; Zou, Long (Frontiers in Microbiology, 2023)
Microbial reduction is an effective route to deal with hexavalent chromium (Cr(VI)) contamination in the environment, which can significantly mitigate the biotoxicity and migration of this pollutant.The present study investigated the influence of environmental factors on aqueous Cr(VI) removal by a newly isolated facultative anaerobic bacteria Exiguobacterium sp. PY14, and revealed the reduction mechanism. This strain with a minimum inhibitory concentration of 400 mg/L showed the strongest Cr(VI) removal capacity at pH 8.0 because of its basophilic nature, and which was obviously depressed by increasing the Cr(VI) initial concentration under both aerobic and anaerobic conditions. While the removal rate constant for 50 mg/L of Cr(VI) under anaerobic condition (1.82×10 -2 h -1 ) was 3.3 times that under aerobic condition. The co-existence of Fe(III) and Cu(II) significantly promoted the removal of Cr(VI), while Ag(I), Pb(II), Zn(II) and Cd(II) inhibited.Electron-shuttling organics such as riboflavin, humic acid and anthraquinone-2,6-disulfonate promoted the Cr(VI) removal to varying degrees, and the enhancement was more significant under anaerobic condition. The removal of aqueous Cr(VI) by strain PY14 was demonstrated to be due to cytoplasmic rather than extracellular reduction through analyzing the contributions of different cell components, and the end products existed in the aqueous solution in the form of organo-Cr(III) complexes. Several possible genes involved in Cr(VI) metabolism, including chrR and chrA that encode well-known Chr family proteins responsible for chromate reduction and transport, respectively, were identified in the genome of PY14, which further clarified the Cr(VI) reduction pathway of this strain. The research progress in the influence of crucial environmental factors and biological reduction mechanism will help promoting the potential application of Exiguobacterium sp. PY14 with high adaptability to environmental stress in Cr(VI) removal in the actual environment.